Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1155/2019/6326517
|View full text |Cite
|
Sign up to set email alerts
|

Increased HIF-1α in Knee Osteoarthritis Aggravate Synovial Fibrosis via Fibroblast-Like Synoviocyte Pyroptosis

Abstract: Fibroblast-like synoviocytes (FLSs) are the main effector cells of knee osteoarthritis (KOA) synovial fibrosis. Our last report showed that NLRP1 and NLRP3 inflammasomes may mediate LPS/ATP-induced FLSs pyroptosis in KOA. In the present study, we found an elevated hypoxia-inducible factor-1α (HIF-1α) level in the synovial tissue of KOA model rats, and inhibiting the increase of HIF-1α could improve synovial fibrosis in rats. Subsequently, we established LPS/ATP-induced model in FLSs mimicking the inflammatory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
75
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 71 publications
(87 citation statements)
references
References 29 publications
2
75
0
1
Order By: Relevance
“…Gasdermin E is a member of a family of proteins that facilitate necrotic programmed cell death (pyroptosis) following cleavage by caspase-3 56 . Pyroptosis has recently been shown to promote knee osteoarthritis 57,58 , and upregulation of Gsdme in high-grade osteoarthritis cartilage ( Figure 5), supports a role for gasdermin E in disease progression. Ccdc6 -/mice had increased articular cartilage surface damage affecting the medial compartment ( Supplementary Tables 3, 4 and 6).…”
Section: And 6)mentioning
confidence: 63%
“…Gasdermin E is a member of a family of proteins that facilitate necrotic programmed cell death (pyroptosis) following cleavage by caspase-3 56 . Pyroptosis has recently been shown to promote knee osteoarthritis 57,58 , and upregulation of Gsdme in high-grade osteoarthritis cartilage ( Figure 5), supports a role for gasdermin E in disease progression. Ccdc6 -/mice had increased articular cartilage surface damage affecting the medial compartment ( Supplementary Tables 3, 4 and 6).…”
Section: And 6)mentioning
confidence: 63%
“…In our last studies, the correlation between the NLRP inflammasomes and synovial fibroblast pyroptosis was investigated in vivo and in vitro [13]. We also revealed that increased hypoxia-inducible factor-1 α in KOA aggravates synovial fibrosis via synovial fibroblast pyroptosis [14].…”
Section: Introductionmentioning
confidence: 99%
“…In the first 14 days, ten rats in the normal group were injected with 50 ul sterilized physiologic saline, and the KOA model was constructed by MIA as previously mentioned, using both knees. 22 From the 14th day, Chrysin (oscillated dissolved in 0.5% sodium carboxymethylcellulose (CMC) overnight) was administered by intragastric administration. The normal group and the MIA group were administered 0.5% CMC as the control, and each rat in the MIA+Chrysin group was treated with a dose of 10 mg/kg Chrysin.…”
Section: In Vivo Animal Experimental Designmentioning
confidence: 99%